Scholarly Communication Librarianship and Open Knowledge - Bonn, Maria; Bolick, Josh; Cross, Will (Open textbook library., 2023)
The intersection of scholarly communication librarianship and open education offers a unique opportunity to expand knowledge of scholarly communication topics in both education and practice. Open resources can address the gap in teaching timely and critical scholarly communication topics—copyright in teaching and research environments, academic publishing, emerging modes of scholarship, impact measurement—while increasing access to resources and equitable participation in education and scholarly communication. Scholarly Communication Librarianship and Open Knowledge is an open textbook and practitioner’s guide that collects theory, practice, and case studies from nearly 80 experts in scholarly communication and open education. Divided into three parts: What is Scholarly Communication? Scholarly Communication and Open Culture Voices from the Field: Perspectives, Intersections, and Case Studies The book delves into the economic, social, policy, and legal aspects of scholarly communication as well as open access, open data, open education, and open science and infrastructure. Practitioners provide insight into the relationship between university presses and academic libraries, defining collection development as operational scholarly communication, and promotion and tenure and the challenge for open access.